Impact Of Oil Palm Plantation Vs Swamp Buffalo Breeders In Kuripan District Barito Kuala Regency South Kalimantan Province Indonesia - ., Rochgiyanti; Susanto, Heri; ., Jumriani; ., Ardiyansah (Journal of Ecohumanism, 2024)
This paper offers a general survey of the social and environmental impacts associated with oil palm development, on communities by emphasising the negative impacts of oil palm plantation expansion specifically on the hadangan farmers of Kuripan Sub-district, Barito Kuala District, South Kalimantan Province. This is followed by a brief overview of the case study location and the research methodology adopted for data collection. This is followed by presenting the findings from the field research. The paper concludes with reflections on the conclusions and implications of oil palm plantation development in Kuripan Sub-district, Barito Kuala District, South Kalimantan Province.